ANALISIS PENGGUNAAN BINANCE DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Andika Fanani; Wuryaningsih (LPPM Universitas Adiwangsa Jambi, 2025)
Crypto investment in Indonesia has experienced significant acceleration in recent times. Binance, as one of the leading crypto exchanges globally, is now the main option for many investors thanks to its comprehensive services. This research utilizes the Technology Acceptance Model (TAM) framework to examine how user attitudes influence the intention to use the Binance application, while also examining the role of perceived usefulness, ease of access, and risk on these attitudes. Data was collected through a survey of 132 Binance users in Indonesia, then analyzed quantitatively using the Partial Least Squares (PLS) method in Structural Equation Modeling (SEM). The research findings show a positive and significant relationship between user attitudes and perceived usefulness. Meanwhile, perceived risk and ease of use do not have a significant effect on attitudes. In addition, the mental orientation of users has a strong influence on the desire to use Binance constructively. These findings indicate that, in the context of digital asset platforms such as Binance, perceived usefulness is a key factor in shaping positive user attitudes. This research contributes theoretically to the development of technology adoption models and offers practical insights for crypto service providers and regulators in formulating strategies to enhance user adoption